Pre-split blasting design to reduce costs and improve safety in underground mining - Pomasoncco-Najarro, Alexander (2022)
To control the overbreaking of an underground mining development gallery, the controlled blasting technique was proposed and as a result it was possible to reduce costs and improve the physical stability of the periphery of the opening, achieving greater safety for personnel and equipment. With the support of the geomechanical studies, the rock quality of the advancing front was determined, serving for the design of the drilling mesh and the choice and distribution of the explosives in the respective drills. This study demonstrates that it is possible to make progress in efficient mining preparation and development work, achieving minimal damage to the roof and walls of the mining work. Performing the simulation with the software determines a difference between conventional blasting with the design of the pre-cut technique, optimizing the parameters of the perforation mesh, selection of the explosive charge, the order of detonation. As a result, the study found a 60%–70% reduction in excess excavation, showing a better finish of the tunnel contour, yielding a 16% reduction in support costs.